Optimizing the “Time to pregnancy” in women with multiple sclerosis: the OPTIMUS Delphi survey - Carbone, Luigi; Landi, Doriana; Di Girolamo, Raffaella; Anserini, Paola; Centonze, Diego; Marfia, Girolama Alessandra; Alviggi, Carlo, the Interdisciplinary Group for Fertility in Multiple Sclerosis (IGFMS); Alviggi, Carlo; Di Girolamo, Raffaella; Carbone, Luigi; Lanzillo, Roberta; et al. (Frontiers in Neurology, 2023)
Background: The debate on how to manage women affected by Multiple Sclerosis (MS) during reproductive age is still opened, like the issue of fertility in such patients. Main arguments regard the identification of the optimal window for pregnancy and how to deal with medical therapy before and during conception. The aim of this Delphi consensus was to collect opinions of a multidisciplinary group, involving reproductive medicine specialists and neurologists with experience in the management of Multiple Sclerosis women with reproductive desire. Methods: Four experts plus Scientific Coordinators developed a questionnaire distributed online to 10 neurologists and later discussed the responses and amended a list of statements. The statements were then distributed via an online survey to 23 neurologists (comprising the first 10), who voted on their level of agreement/disagreement with each statement. Consensus was achieved if agreement or disagreement with a statement exceeded 66%. Results: Twenty-one statements reached consensus after 2 rounds of voting, leading to the following main recommendations: 1) Fertility evaluation should be suggested to wMS, in case of need to shorten time to pregnancy and before treatment switch in women on DMTs contraindicated in pregnancy, particularly in case of highly active disease and age >35 years. 2) ART should not be discouraged in wMS, but use of DMTs until pregnancy confirmation should be suggested; ART may be considered in order to reduce time to pregnancy in MS women with a reduced ovarian reserve and/or age >35 years, but in case of expected poor ART prognosis and need of more than one ART cycle, a switch to a high-efficacy DMD before ART should be offered. 3) Oocyte cryopreservation may be considered in women with reduced ovarian reserve, with unpredictable time to complete diagnostic workup and achieve disease control; a risk/cost benefit analysis must be performed in women >35 years considering the diminished ovarian reserve. Conclusions: This consensus will help MS neurologists to support family planning in wMS, respecting MS therapeutic needs but also taking into account the safety and impact of advancing age on fertility.